Self-reporting of adverse drug reactions of nonsteroidal anti-inflammatory drugs in community pharmacies - Phayom Sookaneknun Olson; Janet Krska; Chatmanee Taengthonglang; Pinyapat Tansin; Wilasinee Siangtrong; Piyatida Pongrueangdilok; Narumol Jarernsiripornkul; Pemmarin Potisarach (Journal of Pharmaceutical Policy and Practice)
Background Ibuprofen and diclofenac are nonsteroidal anti-inflammatory drugs widely used worldwide. Spontaneous reporting often results in an underestimation of the incidence of adverse drug reactions (ADRs), and a few studies have been conducted in community settings, particularly in community pharmacies. This study aimed to determine the frequency and characteristics of short-term ADRs associated with ibuprofen and diclofenac in community pharmacy patients.Methods This prospective cohort study was conducted in 15 community pharmacies. A questionnaire from a previous study was modified and tested for content validity. Community pharmacists distributed the questionnaire after dispensing ibuprofen or diclofenac and followed non-responders via telephone and online media platforms. The returned questionnaires were assessed for causality by a pharmacist and three researchers. Descriptive analyses and comparisons between reports on ibuprofen and diclofenac were performed using chi-square and independent t-tests for appropriate outcomes.Results Of the 590 distributed questionnaires, 279 were included in the analysis. The percentage of participants who reported ADRs to ibuprofen and diclofenac was 33.3%. Among participants with suspected ADRs, the average number of suspected ADRs from diclofenac was higher than from ibuprofen; however, no significant difference was observed (5.5 ± 8.9 and 3.1 ± 3.0, p > 0.05). Of the 347 self-reported ADRs, 45.2% were assessed as probable and possible ADRs. The highest rate of suspected ADRs was in Mental Health (14.4%), followed by the Nose, Throat, Neck, or Voice (9.8%), and the Stomach or Digestive Systems (8.9%), respectively.Conclusions Diclofenac showed more suspected ADRs than ibuprofen in a community setting. Almost half of the self-reported ADRs were assessed as probable or possible. Strategies for sustaining community pharmacists in monitoring patients and reporting ADRs should be supported.